2018
DOI: 10.1515/jpm-2018-0172
|View full text |Cite
|
Sign up to set email alerts
|

Neonatal Ogg1/Mutyh knockout mice have altered inflammatory gene response compared to wildtype mice in the brain and lung after hypoxia-reoxygenation

Abstract: For the first time, we report that Ogg1 and Mutyh in combination protect against late inflammatory gene activation in the hippocampus/striatum and lung after neonatal hypoxia-reoxygenation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 38 publications
0
3
0
Order By: Relevance
“…Previous studies demonstrating an inflammation promoting role of OGG1 may provide clues for how this protein functions in AP. Animal models in which OGG1 has been shown to promote inflammation include contact hypersensitivity (skin inflammation; [ 18 ]), endotoxin shock (generalized, “whole body” inflammation) [ 18 ], asthma [ 46 ], Pseudomonas infection [ 47 ], hypoxia-reoxygenation-induced neuroinflammation [ 48 ] and TNF-induced lung inflammation [ 23 ]. Given the central role of NF-κB signaling in AP we considered this pathway as the most likely target of the OGG1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrating an inflammation promoting role of OGG1 may provide clues for how this protein functions in AP. Animal models in which OGG1 has been shown to promote inflammation include contact hypersensitivity (skin inflammation; [ 18 ]), endotoxin shock (generalized, “whole body” inflammation) [ 18 ], asthma [ 46 ], Pseudomonas infection [ 47 ], hypoxia-reoxygenation-induced neuroinflammation [ 48 ] and TNF-induced lung inflammation [ 23 ]. Given the central role of NF-κB signaling in AP we considered this pathway as the most likely target of the OGG1 inhibitor.…”
Section: Discussionmentioning
confidence: 99%
“…In turn, this inflammation can enhance acute allograft rejection, impair transplant tolerance and accelerate the progression of chronic rejection ( 25 ). A number of reports in cellular and animal models have shown that the levels of inflammatory factors, including IL-6 and IL-1β, were significantly increased after lung injury, whereas those of immunosuppressive factors, including IL-10, were decreased ( 26 , 27 ). Therefore, it is necessary to reduce the occurrence of inflammation to mitigate the damage induced by LIRI.…”
Section: Discussionmentioning
confidence: 99%
“…The transcriptome of neonatal OGG1 −/− / MUTYH −/− mice was recently investigated after brain hypoxia reoxygenation, where altered gene expression patterns of inflammatory markers in the hippocampus/striatum were detected [ 110 ]. These results raise the hypothesis that OGG1 / MUTYH -mediated transcriptional regulation is important for brain stroke outcomes.…”
Section: Impact Of Dna Glycosylases On Acute Tissue Damage and Regeneration During Brain Injurymentioning
confidence: 99%